A new bulbil-bearing species of Arisaema sect. Anomala from Vietnam - Nguyen-Phi, Nga; Tran, Ngoc Toan; Tran, Huu Dang; Van, Hong Thien; Pham, Tai Minh; Nguyen-Le, Xuan Bach; Luu, Hong Truong (Phytotaxa, 2025)
A new species of Arisaema (Araceae), A. bulbilferum, is described from Ba Na – Nui Chua Nature Reserve, Da Nang City, Central Vietnam. The species belongs to section Anomala, characterized by its evergreen habit, rhizomatous stem, trifoliolate leaves, and spadix appendix densely covered with filiform neuter flowers. Arisaema bulbilferum is distinguished by its unique vegetative reproduction via bulbils formed at the apex of the petiole – an uncommon trait within the genus. It is morphologically similar to A. pingbianense but differs in rhizome length, peduncle-to-petiole ratio, petiole and peduncle color patterns, structure of sterile spadix’ appendix, ovary and fruit shape, and a distinctive white spot on the spathe that spreads from the base of the limb to the back of the tube. Conservation assessments classify A. bulbilferum as Endangered (EN) under IUCN criteria. With this discovery, section Anomala now comprises 14 species recorded in Vietnam, further confirming the region’s rich diversity of Arisaema. A key to all known species of Arisaema sect. Anomala in Vietnam is provided.